Impact Innovation Logistics, Collaboration Between Mode and Government Regulation on The Competitiveness of Freight Forwarding Companies - Tohir, Muhammad; Primadi, Andri; Adhitya Kurniawan, Indra (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
Multimoda transportation (MTO) can be interpreted as a method of transporting cargo from one location to another using at least two or more different modes of transportation. The main principle of multimodal transportation is that there is only one bill of lading even though it involves several modes of transportation such as air, rail, land or sea. Multimodal transportation activities, in accordance with Ministerial Regulation No. 8 of 2012, can only be held by multimodal transport business entities, both national and foreign business entities. In carrying out multimodal transportation activities, the MTO business entity is responsible for supporting multimodal transportation activities which include managing transportation, warehousing, cargo consolidation, provision of cargo space, and customs for multimodal transportation to and from abroad. For a business entity, a business license or legality is a form of obedience to the law. The legality referred to here is a legally valid permit for all business activities carried out. All national MTO business entities must be able to provide multimodal transportation services that meet applicable safety and security standards. In order to guarantee the realization of effectiveness and efficiency in the implementation of the national logistics system, it is necessary to ensure that every MTO organizing business entity has fulfilled the legality aspect in accordance with the applicable regulations. This study aims to review the legality of operating multimodal transport operators in realizing the effectiveness of the national logistics system in order to determine the legality of operating multimodal transport in the Denpasar area. The data collection technique in this study is by means of literature studies and surveys (questionnaires and interviews) which will then be analyzed using a qualitative descriptive analysis method.